2001
DOI: 10.1152/ajplung.2001.280.3.l390
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced changes in chromatin structure and in vivo footprints in the inducible NOS promoter

Abstract: Transcription of the human inducible nitric oxide synthase (iNOS) gene is regulated by inflammatory cytokines in a tissue-specific manner. To determine whether differences in cytokine-induced mRNA levels between pulmonary epithelial cells (A549) and hepatic biliary epithelial cells (AKN-1) result from different protein or DNA regulatory mechanisms, we identified cytokine-induced changes in DNase I-hypersensitive (HS) sites in 13 kb of the iNOS 5'-flanking region. Data showed both constitutive and inducible HS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…DNase I Hypersensitivity-DNase I hypersensitivity assays were performed as described previously (48). Briefly, HK-2 cells were treated with hemin (5 M) or vehicle (Me 2 SO) for 2 h. Cells were collected and nuclei isolated.…”
Section: Methodsmentioning
confidence: 99%
“…DNase I Hypersensitivity-DNase I hypersensitivity assays were performed as described previously (48). Briefly, HK-2 cells were treated with hemin (5 M) or vehicle (Me 2 SO) for 2 h. Cells were collected and nuclei isolated.…”
Section: Methodsmentioning
confidence: 99%
“…In diabetic vascular disease, altered histone modifications may mediate the metabolic changes and proinflammatory alterations in SMCs (132). Not only is cytokine expression under epigenetic control, but cytokines themselves also induce (indirect) changes to the chromatin, providing an essential link between inflammation and epigenetic programming (89).…”
Section: Histone Modificationmentioning
confidence: 99%
“…Cell permeabilization, DNase I treatment, and Southern analysis were performed as previously described ( 37,38 ). Following DNase I treatment, cell lysates were incubated overnight at 50°C, and genomic DNA was isolated by organic extraction, alcohol precipitation, and resuspension in TE.…”
Section: Dnase I Hypersensitive (Hs) Site and Southern Blot Analysismentioning
confidence: 99%
“…1 ) illustrate a constitutive DNase I HS site at ‫ف‬ 9.0-10 kb upstream of the transcriptional start site. We have previously shown that constitutive HS sites harbor specifi c inducible elements ( 37,45 ); therefore, we chose to further analyze this region.…”
Section: ␣ Enhancermentioning
confidence: 99%